Achieving Superplasticity in Ultrafine-Grained Mg-9Li Alloy via Dual-Phase Microstructure Optimization - Jiahao Xu; Xinyue Gong; Wanxiang Zhao; Chao Sun; Guibin Shan; Huan Liu; Dan Song (Metals)
In this study, high toughness and superplastic deformability were achieved in Mg-9Li alloys through dual-phase microstructure optimization. Solid solution (SS) and equal channel angular pressing (ECAP) treatments were employed to refine the alloy’s microstructure. The effects of these treatments on room-temperature and low-temperature high-strain-rate superplasticity were systematically investigated under varying microstructural conditions. Results demonstrate that the SS-ECAP alloy exhibits outstanding superplasticity at room temperature and remarkable high-strain-rate deformation capability, achieving a maximum fracture elongation of 602.1%. Grain refinement and reduced dislocation density promote uniform void nucleation under high strain. Calculations of the strain rate sensitivity index (m-value) and activation energy (Q) reveal that the superplastic behavior in the SS-ECAP state is predominantly governed by grain boundary sliding facilitated by grain boundary diffusion. These findings provide critical insights into advancing the superplastic forming technology of Mg-9Li alloys.